Interesting case of esophageal perforation due to foreign body - Padam Kumar Bhawarlal; Gnanasekar Murugaiyan; Saravana Krishna Raj; Mohan Venkataraman; . Gopalakrishnan; Jeykumar Thirukonda; Pranesh Ravichandran (Journal of Association of Pulmonologist of Tamil Nadu, 2021)
A 75 year old gentleman, who is a chronic heavy smoker and edentulous person who used to swallow his food rather than proper mastication, presented with chest pain and dysphagia. CT scan revealed foreign body penetrating the oesophagus and invading the mediastinum leading to a mediastinal collection. Upper gastrointestinal endoscopy to remove the foreign body was not successful, and hence open surgery was done by specialist in thoracic and surgical Gastroenterology. The foreign body was removed successfully and treated with appropriate antibiotics. Patient was discharged home as per plan and followed up in out patient clinic. He has been keeping well.